DOI: 10.11606/t.5.2014.tde-12012015-130033
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação e tratamento de pacientes com dor facial atípica através da estimulação magnética transcraniana repetitiva

Abstract: RESUMO As características funcionais e morfológicas da face, aliadas à complexidade do fenômeno doloroso, tornam favorável a existência de inúmeras fontes de dor facial, como procuraram demonstrar as várias classificações existentes a respeito. A nucleotratotomia trigeminal consiste na ablação cirúrgica de núcleos trigeminais de segunda ordem e tratos. Dois casos de dor facial atípica refratários ao tratamento medicamentoso ou a outras formas não-operatórias são discutidos. A intensidade da dor pré e pós-opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 81 publications
(130 reference statements)
0
9
0
Order By: Relevance
“…Umezaki et al, 2015 [48] reported the occurrence of headache at the beginning of treatment, which disappeared within two days in seven participants in the active group and in five participants in the sham group. Khedr et al, 2005 [35] reported an absence of adverse effects, while Galhardoni et al, 2014 [30] did not describe any evaluation of side effects in their study. The adverse effects reported in each tDCS /TMS article are summarized in S1 Table.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Umezaki et al, 2015 [48] reported the occurrence of headache at the beginning of treatment, which disappeared within two days in seven participants in the active group and in five participants in the sham group. Khedr et al, 2005 [35] reported an absence of adverse effects, while Galhardoni et al, 2014 [30] did not describe any evaluation of side effects in their study. The adverse effects reported in each tDCS /TMS article are summarized in S1 Table.…”
Section: Resultsmentioning
confidence: 96%
“…Galhardoni et al, 2014 [30]; Khedr et al, 2005 [35]; Lindholm et al, 2015 [34] and Umezaki et al, 2015 [48] evaluated the efficacy of repetitive TMS (rTMS) in the treatment of neuropathic orofacial pain, including BMS, AFP and TN. The stimulation protocols differed in the number of sessions, site of the stimulation, and the intensity and number of pulses per session.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations